Social science research methods in contemporary liturgical research: an introduction - Lloyd, Trevor; Steven, James; Tovey, Phillip (Joint liturgical studies, 2010)
Preface -- Introduction: Social science research methods and liturgy -- Literature review and document analysis -- Surveys and questionnaires -- Participant observations -- Interviews -- Action research -- Research ethics -- Conclusion